Best loved books for young readers (Pleasantville, N.Y. : Reader's Digest Association, 1966)
A multivolume collection containing condensations of such works as Robinson Crusoe, Green Mansions, Cry, the Beloved Country, and The Red Badge of Courage.
Keywords: Condensed books; Children's literature; Literature -- Collections